Analisis Penerapan Diagnosis Keperawatan NANDA, NOC, NIC pada Pasien Benigna Prostat Hypertropy Postoperasi Trans Uretral Resection Prostat - Widiastuti, Widiastuti; Pangastuti, Heny Suseani; Alim, Syahirul (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2007)
Please refer to the file